Culture, Power Relations and Development of the Architectural Style: The Planning Precedent of Denpasar City - Ida Bagus Gde Wirawibawa; I Dewa Gede Agung Diasana Putra (Pusat Kajian Bali Universitas Udayana, 2023)
A work of architecture has historical significance and serves as a cultural artifact. This work reflects the personality of a specific neighborhood or city. Identity carries a variety of connotations because it is a fundamental and necessary aspect of upholding cultural values and a nation's dignity. Rapid urbanization, on the other hand, frequently results in regional development that is unrelated to the region's historical factors or the sustainability of the region's culture. This paper seeks to establish an architectural precedent for developing a city area cultured as a heritage city by conducting field surveys and graphically analyzing architectural documents, as well as a historical analysis of power relations in the Denpasar urban area, particularly the former Denpasar palace area. In this case, a combination of traditional and colonial architectural styles is used as a design reference and precedent for the future development of urban areas.